The Influence of Promotions, Prices and Location on Customer Loyalty of The Beverage Industry in Bogor City - Sitorus, Astrid Napita; Supriandi, Supriandi; Sasmito, Priyo (Westscience Press, 2023)
This study aims to examine the effect of promotion, price, and location on customer loyalty in the beverage industry in Bogor City, Indonesia. This study used a quantitative research design, and data was collected from 300 respondents using survey questionnaires. The data was analyzed using SPSS software. Research findings show that promotions, prices, and locations have a significant positive influence on customer loyalty in the beverage industry in Bogor City. The study's findings have significant implications for beverage companies in Bogor City, as it highlights the need for effective marketing strategies that focus on promoting their products, balancing prices, and optimizing their store locations. The study's findings also have implications for future research in the area of customer loyalty in the beverage industry. Future research may examine the influence of other marketing strategies such as product quality, customer service, and brand reputation on customer loyalty. Future research can also explore the effect of customer satisfaction and trust on customer loyalty.